Edukasi Cegah Anemia pada Remaja Putri dengan Konsumsi Tablet Tambah darah dan Kurma di Kelurahan Sungai Putri Kota Jambi - Julaecha Julaecha; Armina Armina; Ajeng Galuh Wuryandari (Universitas Baiturrahim, 2026)
Teenagers entering puberty are at high risk of iron deficiency anemia, a condition caused by iron loss during menstruation. This risk increases if dietary iron intake is insufficient. During menstruation, women lose significant amounts of iron-rich blood, reducing their ability to transport oxygen throughout the body. This can lead to symptoms such as fatigue, dizziness, tiredness, and decreased concentration, which can disrupt daily activities. Providing iron-fortified tablets (IBT) to adolescent girls is one way to address anemia. 80.9% of adolescent girls receive IBT at school, but only 1.4% consume IBT. Survey results show that 95% of adolescents do not consume IBT, and 5% consume IBT but irregularly, citing a lack of symptoms of anemia and the effects of IBT. This community service project aims to provide knowledge about anemia and how to prevent it by consuming IBT and, as a complementary therapy, consuming milk dates to prevent anemia. The method in this activity is lecture, question and answer, the media used is leaflet, the duration of the activity is 60 minutes. This activity was carried out at the Youth Posyandu, Sungai Putri Village, located in the Sungai Putri Village Office Hall, Jambi City in May-July 2023, attended by 40 female participants. An assessment of knowledge about anemia and how to prevent it was carried out before and after counseling using a questionnaire. The results of filling out the questionnaire showed that the average knowledge of adolescents about anemia and its prevention before being given education was 61.88 and after being given education there was an increase in the average knowledge score to 78.25. Providing education can increase this knowledge due to the structured transfer of information, the use of appropriate media and active involvement of participants.